The influence of cultural dimensions on entrepreneurial intention in Madagascar's rural areas - Ratsimanetrimanana, Fenosoa A. (My University, 2014)
Understanding the triggers of the intention was, is and will be at the heart of scholars’ preoccupations when dealing with the universe of entrepreneurship. This unique pioneering research aimed at comparing the Malagasy main ethnic groups in terms of measures of cultural dimensions and perceived desirability and examining the effects of this perceived desirability on the relations between cultural dimensions and entrepreneurial intention. A non-experimental cross-sectional survey, based on a cluster sampling with quota approach comprising three sub-samples of ethnic groups and a structured questionnaire directly administrated by trained interviewers, was the source of data of the research. The use of relevant robust statistical tests characterised the data processing of the research, which revealed that there is no important difference in the measures of cultural dimensions among main ethnic groups in Madagascar’s rural areas. The level of perceived desirability and the relationships between cultural dimensions and entrepreneurial intention are not importantly moderated by perceived desirability among the main ethnic groups in Madagascar’s rural areas. Furthermore, it has been discovered that to some extent, Madagascar would not be a country of ethnic diversity and beginning to understand the Malagasy entrepreneurial profile based on cultural dimension, perceived desirability and entrepreneurial intention is possible. Within the context of an unprecedented level of poverty of the population of Madagascar, which strangles the way to a harmonious and sustainable development, the findings of the research would make an invaluable contribution to the setting up or the refining of policies and strategies targeting the promotion of entrepreneurship in general and self-employment in particular. It is broadly acknowledged that the key to alleviating poverty is based on the encouragement of self-employment of all individuals.
Keywords: Madagascar; Ethnic groups; Entrepreneurship; Economic conditions; Poverty